Membumikan Hukum Positif Indonesia Bercorak Hukum Islam - Budi Sastra Panjaitan (DOKTRINA: JOURNAL OF LAW, 2021)
Indonesian positive law with Islamic law is a step in realizing Indonesianness in the sense of having an Indonesian personality and sense of nationality, besides that, Indonesian positive law with Islamic law also has a noble goal, namely achieving justice. The purpose of this study is to find out the relationship between Indonesian positive law which is characterized by Islamic law in relation to justice. The research method used is a normative legal research method. The realization of Indonesia's positive law with Islamic law is in fact very much in line with the first principle of Pancasila, namely Belief in One God. Omnibus law is an opportunity in realizing positive Indonesian law with Islamic law, especially in improving the status and aligning KHI with various sectoral laws and regulations, these opportunities and challenges must be captured not only by experts in Islamic law in Indonesia but also by the Faculty of Sharia. 'ah in Indonesia, not only by the State Syari'ah Faculties but also by the Private Syari'ah Faculties.